Maatalouden tulomuutokset tyypillisillä maatalousvaltaisilla alueilla - Oksa, Anna-Liisa (Maatalouden taloudellinen tutkimuslaitos, 1997)
The purpose of the study was to examine the income changes in agriculture in 1994-2000 and the changes in the accrued taxes in two different kinds of areas in which agriculture has a significant role. The income from agriculture has been expected to fall due to the decrease in the national aid to such an extent that it may be necessary to assess agriculture as a source of income from completely new starting points on almost all farms. The actions of farmers influence the employment situation of the area in question, and income changes in agriculture are reflected in the business activities and accrued taxes. In areas dominated by agriculture, changes in farmers income have a greater effect on the regional economies than in areas with a wider spectrum of industries. The areas concerned represent a typical milk production area in Central Finland and a plant production area in Southwestern Finland with relatively good production conditions. An attempt has been made to obtain as simplified a view of the income changes in agriculture as possible by choosing an area typical of the production line in question for the study, while similar farms can be found in other parts of the country, too. The study is connected to the project Adjustment to the EU membership in areas typically dominated by agriculture , which is a joint project of the Agricultural Economics Research Institute, Institute for Upper Savo Studies, and Pyhäjärvi Institute, financed from the MATEUS research project concerning the adjustment of agriculture and horticulture to the EU. The study is based on accounts of the structure of industries and the role of agriculture in this in the areas in question prepared at the regional institutes in autumn 1995. In the early part of 1996 an extensive farmer survey was conducted on the dairy farms in Upper Savo and on pig and plant production farms in Southwestern Finland, and similar interviews were carried out on chicken farms as a separate study. The results based on the research data are presented in this paper. The study is concerned with agricultural income, other incomes, investments, and accrued taxes on the farms as well as the total amounts of these in the areas in question.
Keywords: Ma; maataloustulo; tulovero; maaseutu; taloudellinen kehitys; farm income; income tax; rural areas; economic development